Simulation test of automotive cylinder head for six stroke engine using computer aided engineering software - Mohd Khalidi, Yahya (2009)
This dissertation deals with durability assessment for new six-stroke cylinder head engine system using variable pressure loadings. The objective of this dissertation is to develop the general procedures for durability assessment on the cylinder head when the pressure applied. The dissertation describes the finite element analysis techniques to predict the failure of the cylinder head and identify the critical locations of the components. Aluminium 356.0-T71 material was studied in this dissertation which commonly used in automotive industry. The structural three-dimensional solid modelling of cylinder head was developed using the solidwork software. The finite element analysis was then performed using MSC.NASTRAN code. The finite element model of the components was analyzed using the linear statics stress analysis. From the results, it is observed that by making mesh optimization, the accuracy of values for stress and displacement will increase. The obtained results indicate that the values stress for cylinder head is under ultimate tensile strength value of aluminium 356.0-T71.The results concluded that the smallest value of mesh size will produce fine mesh. Based on analysis result, the cylinder head design is acceptable to product by using casting method. The durability assessment results are significant to improve the component design at the early developing stage. The results can also significantly reduce the cost and time to market, and improve product reliability and customer confidence of the component.